Human responses to environmental change on the southern coastal plain of the Caspian Sea during the Mesolithic and Neolithic periods. (15th August 2019) - Leroy, S.A.G.; Amini, A.; Gregg, M.W.; Marinova, E.; Bendrey, R.; Zha, Y.; Beni, A. Naderi; Fazeli Nashli, H.
Abstract: This paper presents results of a multidisciplinary research initiative examining human responses to environmental change at the intersection of the southern coastal plain of the Caspian Sea and the foothills of the Alborz Mountains during the terminal Pleistocene and early Holocene. Our palaeo-environmental analysis of two sedimentary cores obtained from a lagoon in close proximity to four caves, occupied by human groups during the transition from hunting and gathering to food-producing ways of life in this region, confirms Charles McBurney's 1968 hypothesis that when Caspian Sea levels were high, Mesolithic hunters were reliant on seal and deer, but as water levels receded and a wide coastal plain emerged, hunters consumed a different range of herbivorous mammalian species. Palynological evidence obtained from these two cores also demonstrates that the cool and dry climatic conditions often associated with the Younger Dryas stadial do not appear to have been extreme in this region. Thus, increasingly sedentary hunting and gathering groups could have drawn on plant and animal resources from multiple ecological niches without suffering significant resource stress or reduced population levels that may have been encountered in neighbouring regions. Our analyses of botanical, faunal and archaeological remains from a recently-discovered open-air Mesolithic and aceramic Neolithic site also shows an early process of Neolithization in the southern Caspian basin, which was a very gradual, low-cost adaptation to new ways of life, with neither the abandonment of hunting and gathering, nor a climatic trigger event for the emergence of a low-level, food-producing society. Highlights: Southern coastal plain of Caspian Sea at foothills of Alborz Mountains. Multidisciplinary analyses of two lagoonal cores and five archaeological sites. Mesolithic and Neolithic period diets linked to changes in Caspian Sea levels. Palynology shows benign Younger Dryas with diverse ecological niches. Multiple lines of evidence for long-enduring process of Neolithization.